The haemodynamics of endovascular aneurysm treatment: a computational modelling approach for estimating the influence of multiple coil deployment. - Kakalis, N; Mitsos, A; Byrne, J; Ventikos, Y (2008)
This paper proposes a novel computational methodology for modelling the haemodynamic effects of endovascular coil embolization for cerebral aneurysms. We employ high-resolution 3-D angiographic data to reconstruct the intracranial geometry and we model the coiled part of the aneurysm as a porous medium, with porosity decreasing as coils are inserted. The actual dimensions of the coils employed are used to determine the characteristics of the porous medium. Simulation results for saccular aneurysms from the anterior communicating and middle cerebral arteries show that insertion of coils rapidly changes intraaneurysmal blood flow and causes reduction in mural pressure and blood velocity up to stagnation, providing favorable conditions for thrombus formation and obliteration of the aneurysm.